Octreotide ameliorates alendronate-induced gastric injury - ŞENER, GÖKSEL; ELÇİOĞLU, HATİCE KÜBRA (ELSEVIER SCIENCE INC, 2004)
Alendronate causes serious gastrointestinal adverse effects. The aim of this study was to investigate whether octreotide, a synthetic somatostatin analogue, improves the alendronate-induced gastric injury. Rats were administered 20 mg/kg alendronate by gavage for 4 days, either alone or following treatment with octreotide (0.1 ng/kg, i.p.). On, the last day, following drug administration, pilor ligation was performed and 2 h later,rats were killed and stomachs were removed. Gastric acidity and tissue ulcer index values, lipid peroxidation (as assessed by malondialdehyde, MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity as well as the histologic appearance of the stomach tissues were determined. Chronic oral administration of alendronate induced significant gastric damage, increasing lipid peroxidation (37.1 +/- 3.2 nmol/g) and myeloperoxidase activity (57.6 +/- 3.7 U/g), while tissue glutathione levels (0.9 +/- 0.1 mumol/g) decreased. Treatment with octreotide prevented this damage as well as the changes in biochemical parameters (MDA: 23.4 +/- 1.3 nmol/g; MPO: 31.68 U/g; GSH: 1.5 +/- 0.1 mumol/g). Findings of the present study suggest that alendronate induces oxidative gastric damage by a local irritant effect, and that octreotide ameliorates this damage by inhibiting neutrophil infiltration and reducing lipid peroxidation. Therefore, its therapeutic role as a ulcer healing agent must be further elucidated in alendronate-induced gastric mucosal injury. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: alendronate; octreotide; lipid peroxidation; glutathione; myeloperoxidase; SOMATOSTATIN; DAMAGE; PROTECTION; RAT; BISPHOSPHONATES; MANAGEMENT; MELATONIN; STRESS; MUCOSA; MYELOPEROXIDASE